2014
DOI: 10.1158/1541-7786.mcr-14-0291-t
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of Compact Golgi Morphology in Advanced Prostate Cancer Enhances Susceptibility to Galectin-1–Induced Apoptosis by Modifying Mucin O-Glycan Synthesis

Abstract: Prostate cancer progression is associated with up-regulation of sialyl-T antigen produced by β-galactoside α-2,3-sialyltransferase-1 (ST3Gal1) but not with core 2-associated polylactosamine despite expression of core 2 N-acetylglucosaminyltransferase-L (C2GnT-L/GCNT1). This property allows androgen-refractory prostate cancer cells to evade galectin-1 (LGALS1)-induced apoptosis, but the mechanism is not known. We have recently reported that Golgi targeting of glycosyltransferases is mediated by golgins: giantin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
116
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 74 publications
(125 citation statements)
references
References 45 publications
(57 reference statements)
9
116
0
Order By: Relevance
“…2G,H). These data are consistent with previous reports from Golgb1 (giantin) knockdown studies in tissue culture cells showing that Golgb1 is not required for Golgi structural integrity (Petrosyan et al, 2012(Petrosyan et al, , 2014Puthenveedu and Linstedt, 2001;Wong and Munro, 2014).…”
Section: G179ssupporting
confidence: 93%
See 1 more Smart Citation
“…2G,H). These data are consistent with previous reports from Golgb1 (giantin) knockdown studies in tissue culture cells showing that Golgb1 is not required for Golgi structural integrity (Petrosyan et al, 2012(Petrosyan et al, , 2014Puthenveedu and Linstedt, 2001;Wong and Munro, 2014).…”
Section: G179ssupporting
confidence: 93%
“…In particular, siRNA knockdown studies suggest that the C2GnT-M and C2GnT-L synthases in the O-glycosylation pathway use Golgb1 exclusively to target to Golgi membrane, whereas C1GalT1 and ST3Gal1 synthases use Golgb1 and GM130-Grasp65 (also known as Gorasp1) as alternative docking sites (Petrosyan et al, 2012(Petrosyan et al, , 2014Wong and Munro, 2014). O-glycosylation in the Golgi starts with synthesis of the glycoconjugate GalNAc-α1-O-Ser/Thr, known as the Tn antigen.…”
Section: Golgb1 Plays An Important Role In Protein Glycosylationmentioning
confidence: 99%
“…In this study we examined the effect of the presence or absence of KRT1 on the appearance of T-antigen as detected by PNA lectin staining. The presence of C2GnT-M in the Golgi, which is KRT1-dependent, is expected to prevent the masking of the T-antigen with ␣2-3Sia (␣2,3-linked sialic acid) by out-competing ST3Gal1 for the T-antigen (22,59) (Fig. 6A).…”
Section: Krt1 Regulates the Glycosylation Function Of C2gnt-m-mentioning
confidence: 99%
“…This study also demonstrated that Giantin, GM130-GRASP65, and GM130-Giantin are the Golgi targeting sites for GTs in a GT-specific manner. Recently, we also show that in advanced prostate cancer cells, differential Golgi targeting of Gal␤1-3GalNAc␣Ser/Thr:␣2-3-sialyltransferase 1 (ST3Gal1) and core 2 N-acetylglucosaminyltransferase-L/1 (C2GnT-L) determines the susceptibility of these cells to Galectin-1-induced apoptosis (22).…”
mentioning
confidence: 95%
See 1 more Smart Citation